Long-Term Reduction of Short-Wavelength Light Affects Sustained Attention and Visuospatial Working Memory With No Evidence for a Change in Circadian Rhythmicity - Domagalik, Aleksandra; Oginska, Halszka; Beldzik, Ewa; Fafrowicz, Magdalena; Pokrywka, Malgorzata; Chaniecki, Piotr; Rekas, Marek; Marek, Tadeusz (Frontiers in Neuroscience, 2020)
The short-wavelength, i.e. blue light, is crucial for non-image forming effects such as entrainment of the circadian system in humans. Moreover, many studies showed that blue light enhances alertness and performance in cognitive tasks. However, most scientific reports in this topic are based on experiments using short exposure to blue or blue-enriched light and only a few focused on the effects of its reduced transmittance, especially in longer periods. The latter could potentially give insight into understanding if age-related sleep problems and cognitive decline are related to less amount of blue light reaching the retina, as eyes’ lenses yellow with age. In this study, we investigated the effects of prolonged blocking of blue light on cognitive functioning, in particular - sustained attention and visuospatial working memory, as well as on sleep, and melatonin and cortisol levels. A group of young, healthy participants was randomly allocated to either blue light blocking or control group. Depending on the group, participants worn amber contact lenses reducing the transmittance of blue light by approximately 90% or regular contact lenses for a period of four weeks. No changes were observed for measurements related to sleep and sleep-wake rhythm. Dim light melatonin onset, evening levels of melatonin, and morning cortisol answer did not show any significant alterations during BL blockade. The significant effects were revealed both for sustained attention and visuospatial memory, i.e. the longer blocking the blue light lasted, the greater decrease in performance was observed. Additionally, the follow-up session conducted approximately one week after taking off the blue-blocking lenses, revealed that in case of sustained attention this detrimental effect of blocking BL is fully reversible. Our findings provide evidence that prolonged reduction of BL exposure directly affects human cognitive functioning regardless of circadian rhythmicity.